Effect of Socratic Reflection Prompts via video-based learning system on elementary school students' critical thinking skills. (July 2022) - Hsu, Fu-Hui; Lin, I-Hsiu; Yeh, Hui-Chin; Chen, Nian-Shing
Abstract: This study designed a Socratic Reflection Prompts via Video-Based Learning System (SRP-VBLS) and investigated the effects of the SRP-VBLS on elementary school 4th graders' critical thinking skills. Participants were divided into three groups: No-SRPs (n = 46), Receiving-SRPs (n = 42), and Responding-to-SRPs (n = 40). Participants in three groups were pre-and post-tested with a critical thinking assessment particularly designed for assessing elementary school students' critical thinking skills. Results show that the Responding-to-SRPs group and the Receiving-SRPs group significantly outperformed the No-SRPs group regarding their critical thinking skill improvement. It was also found that by responding to the SRPs, one of the critical thinking core skills, the analysis skill, of the students was significantly improved. This finding suggests that the SRP-VBLS is effective in developing elementary school students' critical thinking skills, and requiring students to respond to SRPs is especially beneficial to students' analysis skill enhancement. Implications of the findings for designing a video-based learning system in line with the Socratic reflection prompts are discussed. Highlights: Critical thinking is one of the 21st century vital skills. How to enhance critical thinking skills is important. The Socratic Reflection Prompts via Video-Based Learning System fosters elementary school students' critical thinking skills. Responding to the Socratic reflection prompts benefits students more than receiving the Socratic reflection prompts. Requiring students to respond to the Socratic reflection prompts has a significant effect on enhancing analysis skills. Applying Socratic Reflection Prompts via Video-Based Learning System can break the limits of traditional classroom settings.